PENGARUH CURRENT RATIO, RETURN ON EQUITY, DAN EARNINGS PER SHARE TERHADAP HARGA SAHAM PADA PT BANK BNI Tbk 2010 2019 - Hermawan, Hengki; Anggraini, RR Renny (PROSIDING SENANTIAS: Seminar Nasional Hasil Penelitian dan Pengabdian kepada Masyarakat, 2021)
This study aims to determine the effect of Curren Ratio (CR), Return On Equity (ROE) and Earning Per Share (EPS) on the Share Price of PT Bank Negara Indonesia Tbk 2010 - 2019 "the method used is qualitative by obtaining financial statement data from the official website. BNI then the data is processed using SPSS. The partial test using the t-test Curren Ratio (CR) obtained a comparison that is tcount 0.315 < ttable 2447 and a significant value of 0.764 > 0.05 so that the Curren Ratio (CR) has no effect on the stock price of PT Bank Negara Indonesia (Persero) Tbk in 2010-2019. While the Return On Equity (ROE) comparison is obtained, namely tcount -1.130 < ttable 2.447 and a significant value of 0.302> 0.05 so that Return On Equity (ROE) has no effect on the stock price of PT Bank Negara Indonesia (Persero) Tbk in 2010-2019. Earning Per Share (EPS) is obtained by comparison, namely tcount 2,467 > ttable 2,447 and a significant value of 0.049 < 0.05 so that Earning Per Share (EPS) affects the share price of PT Bank Negara Indonesia (Persero) Tbk in 2010-2019. While the simultaneous test with the F test obtained a comparison of Fcount 9.720 > Ftable 4.76 with a significant value of 0.010 <0.05 indicating that the Curren Ratio (CR), Return On Equity (ROE), and Earning Per Share (EPS), together affect the stock price. at PT Bank Negara Indonesia (Persero) Tbk in 2010-2019.